Average and Risk-Return Analysis of Cryptocurrencies Using ARMA-GARCH Models - Sya’imaa.HS, Audrey Ariij; Parmikanti, Kankan; Riaman, Riaman (International Journal of Global Operations Research, 2023)
Cryptocurrency is a digital currency that is created through encrypted cryptography with complex algorithm and connected to each other on the blockchain system. Cryptocurrencies are widely used as investment instruments for financial assets like stocks. Similar to stocks, cryptocurrencies have a high risk – high returns characteristic, but the fluctuation of cryptocurrencies are more dynamic. Professional investors would do a volatility analysis of cryptocurrencies that potentially give the best returns. Returns assessment usually refers to the average value or expected return, while the estimated investment risk can be seen and analyzed from the volatility value. The study aimed to analyze the average and volatility of cryptocurrencies. This research was a case study done on five cryptocurrencies that are included at Top Gainers of 30 days update lists, in September 2022. The period is January 1, 2019 – September 30, 2022. The ARMA-GARCH models using three types of GARCH models, those are SGARCH(1,1), IGARCH(1,1), and TGARCH(1,1) were used for analysis. Based on the results of this research, the best ARMA-GARCH model for cryptocurrency Quant, XRP, Stellar, Monero, and Decred is ARMA(1,0)-SGARCH(1,1), ARMA(32,0)-TGARCH(1,1), ARMA(0,14)-SGARCH(1,1), ARMA(1,4)-TGARCH(1,1), and ARMA(1,0)-SGARCH(1,1). Best expected return with the lowest volatility value is owned by Monero (XMR). The research can be used by investors as a consideration in investing decision-making to cryptocurrencies.